2006
DOI: 10.2337/dc05-2377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Alternative-Site Glucose Measurements in Patients After Major Cardiac Surgery

Abstract: OBJECTIVE -Tight glycemic control improves outcome in critically ill patients but requires frequent glucose measurements. Subcutaneous adipose tissue (SAT) has been characterized as promising for glucose monitoring in diabetes, but it remains unknown whether it can also be used as an alternative site in critically ill patients. The present study was performed to clinically evaluate the relation of glucose in SAT compared with arterial blood in patients after major cardiac surgery.RESEARCH DESIGN AND METHODS -F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…24 Ellmerer et al established that subcutaneous adipose tissue monitoring is effective in postoperative cardiac surgery patients and can be used to guide intensive insulin dosing. 29 Holzinger et al showed the incidence of hypoglycemia was lower in their study population when CGM was available to the clinical staff. However, CGM did not affect the degree of hyperglycemia when compared to intermittent BG testing, which could possibly be explained by having already achieved tight glycemic control in the intermittent BG testing group.…”
Section: Discussionmentioning
confidence: 99%
“…24 Ellmerer et al established that subcutaneous adipose tissue monitoring is effective in postoperative cardiac surgery patients and can be used to guide intensive insulin dosing. 29 Holzinger et al showed the incidence of hypoglycemia was lower in their study population when CGM was available to the clinical staff. However, CGM did not affect the degree of hyperglycemia when compared to intermittent BG testing, which could possibly be explained by having already achieved tight glycemic control in the intermittent BG testing group.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the data suggest a good correlation in most of the patients but the optimal approach would still be the use of intravenous rather than subcutaneous continuous sensor placement. 43 However, the first commercially available intravascular sensors are only now starting to emerge, and their clinical value still needs to be evaluated.…”
Section: How Much Help Can We Get From Novel Technologies?mentioning
confidence: 99%
“…It should be noted that when the results of the CGM were plotted against a blood gas analyzer on an insulin titration grid (showing the correct action with respect to insulin therapy), Ͼ99.1% of the values were in the clinically acceptable treatment zones. 19,20 Sensor Drift CGM sensors all require calibration, some several times a day, to ensure accuracy to meet the manufacturer's specifications. It would be best to calibrate CGM with a CLD or blood gas analyzer, because many of the POC meters lack FDA-required accuracy standards.…”
Section: Accuracymentioning
confidence: 99%